The regulation of omitting the grammar lesson summary - Haj Housen , Helal (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
This research deals with the phenomenon of omitting the preposition by studying and analysingit. This could be done according to the regulation of its noming, which differ to the grammaians term of this phenomenon, and its reasons and indication among these differences are the plenty of using it and the reduction of it. These two reasons are desirable to the Arabs in omitting and briefing of the preposition. At last, there are condition that should available in omitting the pvepositions are good comprehension and non-defaulting or corruption in its meaning. This could be done in accordance with the perspective of the Arabic grammer.